Physical activity and depression of Chinese students in Korea: self-efficacy as a mediator and social support as a moderator - Chang, Pengfei (Frontiers in Psychology, 2025)
IntroductionThis study, grounded in social cognitive theory, investigates the impact of physical activity on depression levels among international students, with a focus on the mediating role of self-efficacy and the moderating effect of social support, aiming to unpack the mechanisms linking physical activity to mental health in this cross-cultural population.MethodsA cross-sectional design was employed, involving 903 international students from two South Korean universities; data were collected via standardized questionnaires and analyzed using SPSS 26.0, with analytical methods including descriptive statistics, correlation analysis, mediation analysis, and moderated regression.ResultsThree key findings were revealed: (1) physical activity exhibited a significant negative correlation with depression levels; (2) physical activity was positively associated with self-efficacy (which in turn negatively correlated with depression), and self-efficacy partially mediated the relationship between physical activity and depression; (3) social support moderated the effect of physical activity on depression.DiscussionThese findings elucidate the underlying mechanisms through which physical activity benefits mental health, highlighting the synergistic roles of self-efficacy (as an internal psychological resource) and social support (as an external buffering factor); the study provides empirical support for integrated interventions combining physical activity promotion, self-efficacy enhancement, and social support reinforcement to mitigate depression among international students, and demonstrates that enhancing self-efficacy and reinforcing social support can significantly amplify the antidepressant effects of physical activity in this group, offering new insights for cross-cultural mental health interventions.